Successful closure of unusual tuberculous esophagomediastinal fistula with endoscopic clips - Albuquerque,Andreia (2013)
A 41-year-old man, on tuberculostatic treatment for three months for disseminated tuberculosis, developed a tuberculous esophagomediastinal fistula, which was successfully closed with endoscopic clips. Use of endoscopic clips in esophageal perforations and closure of fistulas following surgical complications has been described, but to our knowledge there are no previous reported cases of tuberculous esophagomediastinal fistulas managed with clipping. In this case, endoscopic clips associated with tuberculostatic treatment were crucial allowing fistula closure in a symptomatic patient.